The Greek poets : Homer to the present - Constantine, Peter, 1963-; Hadas, Rachel; Keeley, Edmund; Van Dyck, Karen; Haas, Robert (W.W. Norton and Co, 2010)
An extensive volume of Greek poetry includes more than one thousand entries spanning three millenia and many diverse traditions, in an anthology that includes works by such classic and modern writers as Sappho, Pindar, and Seferis.